SELF DISCLOSURE DAN PERFORMATIVITAS KAUM LESBIAN ANDRO PADA MEDIA BARU (TIKTOK) - Andrine Prima Afneta Arzil (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
This research is a scientific analysis of media which is closely related to social practices that occur in society as well as representation of gender identities in digital media. This research was conducted to determine the discourse of self disclosure, physical and appearance performativity, homosexual talk performativity, and sexual activity performativity displayed by lesbian (andro) on her new media accounts (Tik Tok) and how Tik Tok is interpreted as a medium of resistance lesbians today. By using a qualitative research methodology, this study puts itself in a digital ethnographic approach. The data collected in this digital ethnographic study is in the form of in-depth and comprehensive observations of 227 video content uploaded by creators, making transcripts on each content then categorized, and conducting analysis in accordance with research objectives. Through audio-visual that legitimize their performativeness, from here, their identity is formed, reshaped, displayed, and conveyed to the mass audience through self-disclosure. Thus, this actualization event leads to resistance. The body is not only understood as a plate on which sexuality and gender are formed, but gender and sexuality itself are labeled into the body. Identity, then, is formed performatively through discourse. Gender identity is an effect produced by individuals because it displays gender act practices.